Facilitation skills for nurses - F Cilliers; L Terblanche (AOSIS, 2000)
Using the pcrson-centered approach, facilitation in this study was conceptualised as providing opportunities for personal growth in the patient, and operationalised in a skills workshop for 40 nurses from different hospitals in Gauteng. The first objective was to evaluate the workshop and the second to ascertain its effect on the participant's experienced performance. A combined quantitative and qualitative research design was used. The quantitative measurement (Personal Orientation Inventory, Carkhuff scales) indicated that the workshop stimulated self-actualisation in terms of intrapersonal awareness, and the interpersonal skills of respect, realness, concreteness, empathy, as well as in terms of attending and responding behaviour. The qualitative measurement (a semi-structured interview) indicated that the participants were able to empower patients to find their own answers to difficult personal questions. The alternative hypothesis was accepted, namely that this workshop in facilitations skills significantly enhanced the intra- and interpersonal characteristics associated with self-actualisation and the facilitation of growth in patients. The findings highlighted the difference between the two roles of instructor and facilitator, and recommendations to this effect were formulated.